Teknologi Informasi Percepatan Pelayanan Publik Pembuatan Paspor pada Kantor Imigrasi - Nurmalasyiah, Nurmalasyiah (Jurnal Ilmiah Administrasi Publik, 2016)
The article aims to analyze the acceleration of information technology in public service to the community in term of making a passport which organized by the immigration office. Role of Information Technology is necessary in all elements, such as; institutions, agency, organisation and everyone who related with the service sector. Data from various studies indicate that the use of information technology is very influence to accelerate quality in the public service, especially in the process of passport services. Mastery of Information Technology at the present time has become imperative, more specifically, to the institution including facilitate the administrative work in the public service sector.